Mobility inequality of disadvantaged groups in Greater Cairo region - Nouran Azouz; Marwa A. Khalifa; Mohamed El-Fayoumi (Renewable Energy and Sustainable Development, 2024)
Mobility inequality in the Greater Cairo Region (GCR) affects disadvantaged groups of women, children and adolescents, elderly people, and persons with disabilities. These groups require inclusive mobility arrangements or protection on the streets. The research aims to explore the existing mobility inequality in GCR, considering the lifestyle and physical characteristics of the target disadvantaged groups. The paper reviews the concepts of mobility inequality, disadvantaged groups, and the United Nations standards of adequate urban mobility; which are utilized as a guide for the empirical study. The empirical study applies two qualitative research methods for the primary data collection, which are conducting semi-structured interviews with an introductory sample, and conducting on-site trips/investigations of the urban mobility delivering in GCR. Additionally, general insights and figures are deployed from the secondary data collection in the context of GCR and Egypt. Subsequently, the research demonstrates a sample of the existing mobility inequality experiences, local context realities, and consequential life compromises in GCR. The paper aligns all the results of the respondents’ experiences, preferences, and transport choices. Finally, the paper concludes with key suggestions to tackle the mobility inequality issues in an attempt to enhance the urban mobility experience of disadvantaged groups in GCR.   Received: 12 November 2023 Accepted: 30 December 2023 Published: 12 February 2024